2021
DOI: 10.1097/md.0000000000024859
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for patients with spasticity after stroke

Abstract: Background: The purpose of this paper is to evaluate the effectiveness and safety of electroacupuncture in the treatment of spasticity after stroke. Methods: We will electronically search PubMed, Medline, Embase, Web of Science, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chinese Scientific Journal Database, and Wan-Fang Database from the date of creation to Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Some studies have found that acupuncture for early stroke (12–24 h) can promote the expression of vascular endothelial growth factor (VEGF), which helps to restore oxygen or nutrition supply in the ischemic penumbra [ 19 ]. Acupuncture also provides a beneficial environment for injured tissue, providing a theoretical basis for acupuncture intervention in early stroke [ 20 ]. In the acute phase of ischemia, vasodilator mediators (such as nitric oxide) are the key to reduce infarct focus and related secondary damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that acupuncture for early stroke (12–24 h) can promote the expression of vascular endothelial growth factor (VEGF), which helps to restore oxygen or nutrition supply in the ischemic penumbra [ 19 ]. Acupuncture also provides a beneficial environment for injured tissue, providing a theoretical basis for acupuncture intervention in early stroke [ 20 ]. In the acute phase of ischemia, vasodilator mediators (such as nitric oxide) are the key to reduce infarct focus and related secondary damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 28 ] Clinical studies have shown that the combination of acupuncture and modern rehabilitation techniques can significantly improve the degree of functional recovery after stroke, shorten the course of treatment, reduce complications, and significantly improve the quality of life of patients. [ 13 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Clinical studies have shown that the combination of acupuncture and modern rehabilitation techniques can significantly improve the degree of functional recovery after stroke, shorten the course of treatment, reduce complications, and significantly improve the quality of life of patients. [13,29] In this study, patients with hemiplegia after stroke were treated for 28 weeks using rehabilitation care or a combination of electroacupuncture and rehabilitation. Both groups showed a significant increase in FMA scores related to extremity motor function, a significant increase in BI scores related to activities of daily living, a significant decrease in NDS scores related to disability, and a significant decrease in physiological state (HAMA and HAMD scores) at 28 weeks of treatment when compared to the pretreatment period, suggesting that both interventions improved motor function, neurological function, and activities of daily living in elder patients with hemiplegia after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The simplified Fugl-Meyer assessment (FMA) scale is one of the commonly used criteria to assess the motor function of limbs in clinical practice. 12 The total score of the scale is 100 points, with higher scores indicating better limb motor function. (4) Barthel index scoring method was used to evaluate patients' daily living ability before and after treatment.…”
Section: Evaluation Of Therapeutic Efficacymentioning
confidence: 99%